2022
DOI: 10.4236/ojneph.2022.124042
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Infection and Acute Kidney Injury: About 43 Cases Report Collected at the Nephrology Department of the Farah Polyclinic in Abidjan

Abstract: Background: Acute kidney injury (AKI) is one of the increasingly described complications of coronavirus infection. Objectives: To identify factors associated with death in patients with acute kidney injury (AKI) during Coronavirus disease (COVID-19) in Abidjan, Côte d'Ivoire. Material and Method: This was a monocentric retrospective analytical study of all patients over 18 years of age with AKI during COVID-19 at the Farah Polyclinic in Abidjan, Côte d'Ivoire. AKI was defined and ranked according to Kidney Dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…(10) In SSA and specifically reporting on AKI as the dysfunction, Ibrahim et al reported AKI occurring in 14.6% of their patients while Dolaamas reported higher in 32.6% . (20,21) A report from a hospital-based registry in Ghana showed that 10% of patients admitted with COVID-19 had underlying CKD with AKI in nearly half of the cases. (22) This wide variation in prevalence of the kidney abnormalities is most likely due to heterogeneity in cohorts studied, from variations in definitions and components of kidney dysfunction to methods employed in diagnosis and reporting.…”
Section: Discussionmentioning
confidence: 99%
“…(10) In SSA and specifically reporting on AKI as the dysfunction, Ibrahim et al reported AKI occurring in 14.6% of their patients while Dolaamas reported higher in 32.6% . (20,21) A report from a hospital-based registry in Ghana showed that 10% of patients admitted with COVID-19 had underlying CKD with AKI in nearly half of the cases. (22) This wide variation in prevalence of the kidney abnormalities is most likely due to heterogeneity in cohorts studied, from variations in definitions and components of kidney dysfunction to methods employed in diagnosis and reporting.…”
Section: Discussionmentioning
confidence: 99%